What effects of COVID-19 on regional economic resilience? Evidence from 31 provinces in China - Tian Meng; Congying Tian; Henglong Zhang; Chun Kwong Koo (Frontiers Media S.A., 2022)
After the 2008 global financial crisis, more and more scholars began to focus on economic resilience. In 2020, the outbreak of COVID-19 made the public aware of the importance of regional economies to resist and adapt to external shocks. Based on cross-sectional data from 2020 and 2021, this paper uses causal inference counterfactual to assess the regional economic resilience of various Chinese provinces under the COVID-19 pandemic, and analyzes the determinants of regional economic resilience through geographic detector models. It is found that (1) from the regional perspective, the eastern and central regions are the first to be affected by the epidemic, and their economic resistance is lower than the national average, but the eastern and central regions can stabilize the development trend of the epidemic earlier; (2) from the perspective of provinces, developed provinces are more vulnerable to the epidemic in the early stages than backward provinces; (3) government forces and social environment play an important role in regional economic resistance and adaptation in the initial stage of epidemic impact. Therefore, at the critical moment of China's post-epidemic economic recovery, it should be noted that the regional response to the epidemic depends on the path of action and the specific environment, and cannot be "one-size-fits-all." Pay close attention to the key role of government and the management of risk prevention. The region has established sound public health policies, systems and mechanisms.